Analysis of Autonomous Learning as Method in Learning English: A Case Study - Salamanja, Prasetya Rakhmat Darmawan; Kholis, Adhan (Faculty of Social and Political Sciences University of Bangka Belitung, 2023)
In the modern era, teaching English is the main role for making students be able to get a skill and communicate with foreigners on social media and reality. English teaching needs teachers to teach students to develop both academic and personal abilities of English. English Teachers often used new methods and strategies in learning English and even these methods were often evaluated every week but, why there were still many students who had not been able to understand English in terms of theory and practice. Autonomous learning was a student-centered language learning method in order to be able to practice and that its approach made students autonomy focused on utilizing of cognitive and metacognitive resources to shape the English learning process. The writer uses library research (library research). Library research is research in which data collection techniques are carried out by reading various literature related to information and relevance to the research topic. As for the type of literature research that is being carried out, namely field research, research uses a descriptive type, namely to describe in detail about reality or phenomena by providing criticism or research on these phenomena. The approach used by the author in this study is a qualitative approach. This qualitative approach is used to solve actual problems by collecting, compiling, analyzing and classifying data. Various types of data sources in articles in the form of journals, research reports, scientific magazines, newspapers, relevant books, seminar results, unpublished scientific articles, sources, bibliographical letters, video graphics and so on